Direct fiber comb stabilization to a gas-filled hollow-core photonic crystal fiber - Wu, Shun; Wang, Chenchen; Fourcade-Dutin, Coralie; Washburn, Brian R.; Benabid, Fetah; Corwin, Kristan L. (My University, 2014)
We have isolated a single tooth from a fiber laser-based optical frequency comb for nonlinear spectroscopy and thereby directly referenced the comb. An 89 MHz erbium fiber laser frequency comb is directly stabilized to the P(23) (1539.43 nm) overtone transition of [superscript]12C[subscript]2H[subscript]2 inside a hollow-core photonic crystal fiber. To do this, a single comb tooth is isolated and amplified from 20 nW to 40 mW with sufficient fidelity to perform saturated absorption spectroscopy. The fractional stability of the comb, ~7 nm away from the stabilized tooth, is shown to be 6 × 10[superscript]−12 at 100 ms gate time, which is over an order of magnitude better than that of a comb referenced to a GPS-disciplined Rb oscillator.
Keywords: Optically referenced frequency combs; Direct comb spectroscopy; Fiber lasers